2018
DOI: 10.1017/s1463423618000142
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of community pharmacists’ roles in screening and communication of risks about non-steroidal anti-inflammatory drugs in Thailand

Abstract: Self-administered questionnaires were distributed to all accredited pharmacies in Thailand, inviting the main pharmacist in each pharmacy to participate in this study. Findings Out of 406 questionnaires distributed, 159 were returned (39.2%). Almost all pharmacists claimed to engage in NSAID dispensing practice, but not all of them provided relevant good practice, such as, screening for risk factors (56.3-95.5%), communication on adverse drug reactions (ADRs) (36.9-63.2%) and ADR management (58.9-79.7%), histo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 34 publications
1
22
1
1
Order By: Relevance
“…This practice may lead the public to believe that selective NSAIDs are better and safer to use. Clearly type of NSAID was a factor affecting other aspects of information provision, again confirming some of our survey results . CV side effects were only mentioned by a few participants in relation to selective NSAIDs and not with non‐selective drugs, despite similar risks .…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…This practice may lead the public to believe that selective NSAIDs are better and safer to use. Clearly type of NSAID was a factor affecting other aspects of information provision, again confirming some of our survey results . CV side effects were only mentioned by a few participants in relation to selective NSAIDs and not with non‐selective drugs, despite similar risks .…”
Section: Discussionsupporting
confidence: 87%
“…However, our surveys of Thai health professionals have identified a range of factors affecting self‐reported information provision in addition to the type of NSAID. These include work setting, number of work colleagues, time available for direct patient contact and gender . Our patient survey also found that the duration of NSAID use and age were factors which affected whether or not they had received information about potential side effects and how to avoid or manage these .…”
Section: Introductionmentioning
confidence: 75%
See 3 more Smart Citations